The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.7759/cureus.16103
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Arterial and Venous Thromboembolism in a Patient With Severe Clostridium difficile Infection

Abstract: Most cases of Clostridium difficile infection are hospital acquired; but in recent times, the incidence of community-acquired infections has increased. Patients with Clostridium difficile infections are at an increased risk for thrombosis. We report a case of an 82-year-old female who was admitted to the intensive care unit for acute hypoxic respiratory failure and septic shock. She was found to have Clostridium difficile infection at presentation. During the hospitalization, we discovered bilateral lower extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The authors reported the case of an 82-year-old woman admitted to the emergency area for septic shock secondary to CDI. During the hospitalization, bilateral lower extremity venous thrombosis, pulmonary embolism, multifocal thromboembolic brain infarctions, and acute arterial thromboembolic occlusion of the right upper and lower extremities were detected [72].…”
Section: Incidence Of Vte In Hospitalized Patients With CDImentioning
confidence: 99%
“…The authors reported the case of an 82-year-old woman admitted to the emergency area for septic shock secondary to CDI. During the hospitalization, bilateral lower extremity venous thrombosis, pulmonary embolism, multifocal thromboembolic brain infarctions, and acute arterial thromboembolic occlusion of the right upper and lower extremities were detected [72].…”
Section: Incidence Of Vte In Hospitalized Patients With CDImentioning
confidence: 99%
“…The study found that antidepressant drug use was not correlated with risk of infection; instead, GABAergic drug use (benzodiazepines in particular) was associated (Lalani et al, 2020 ). C. difficile also been shown to result in severe brain infarction and thromboembolism (Kumar et al, 2021 ), but very few information is currently available and further investigations are needed to deeper study the correlation.…”
Section: Microbiota-targeted Strategies Targeting C Diffici...mentioning
confidence: 99%